Neonatal sepsis and resistance pattern of isolates in Tertiary level neonatal unit: Time to evaluate the empirical antibiotics selection - Lubna Ehtizaz, Shahzad Haider, Madiha Fayyaz, Ambreen Ansar, Sajid Nazir, Saima Rafique (Journal of Rawalpindi Medical College, 2021)
Objective: To find out the most common organisms involved in neonatal sepsis origination and observe the pattern of antibiotic sensitivity and resistance of bacterial isolates. Materials and Methods: This descriptive cross-sectional study was conducted at the Department of Paediatrics Izzat Ali Shah Hospital, Wah Cantt. Out of 420 patients admitted with sepsis in NICU, 19.5% of patients with positive blood cultures were included in the study. A consecutive, non-probability sampling technique was used. Results: Out of 82 positive blood cultures gram-positive bacteria were observed in 19 patients (23.2%) and gram-negative bacteria were seen in 63 patients (76.8%). The most common gram-negative pathogens isolated were Acinetobacter (29.3%) and Klebsiella (24.4%). Staphylococcus aureus (12.2%) was the commonest gram-positive organism isolated. Gram-negative organisms showed maximum sensitivity to Tigecycline and Colistin and were resistant to Cefixime, Aztreonam, Amoxicillin, and Ceftriaxone. Gram-positive bacteria were sensitive to Teicoplanin, Linezolid, and Vancomycin while resistance was shown to penicillin and amoxicillin. Conclusion: The current study showed that gram-negative bacteria were the major contributors to sepsis in the respective setup and showed resistance to first-line antibiotics such as Penicillins and Cephalosporins. Strict infection control measures need to be implemented to avoid the emergence of resistant strains of pathogens in NICUs. This will help to reduce the incidence of neonatal sepsis leading to mortality.